Endoplasmic reticulum-targeted delivery of celastrol and PD-L1 siRNA for reinforcing immunogenic cell death and potentiating cancer immunotherapy - Jie Wang; Zilong Zhang; Yan Zhuo; Zhuan Zhang; Rongrong Chen; Li Liang; Xiaohe Jiang; Di Nie; Chang Liu; Zhiwen Zou; Xiang Li; Jiaxin Li; et al. (Elsevier, 2024)
The prospect of employing chemoimmunotherapy targeted towards the endoplasmic reticulum (ER) presents an opportunity to amplify the synergistic effects of chemotherapy and immunotherapy. In this study, we initially validated celastrol (CEL) as an inducer of immunogenic cell death (ICD) by promoting ER stress and autophagy in colorectal cancer (CRC) cells. Subsequently, an ER-targeted strategy was posited, involving the codelivery of CEL with PD-L1 small interfering RNAs (siRNA) using KDEL peptide-modified exosomes derived from milk (KME), to enhance chemoimmunotherapy outcomes. Our findings demonstrate the efficient transportation of KME to the ER via the Golgi-to-ER pathway. Compared to their non-targeting counterparts, KME exhibited a significant augmentation of the CEL-induced ICD effect. Additionally, it facilitated the release of danger signaling molecules (DAMPs), thereby stimulating the antigen-presenting function of dendritic cells and promoting the infiltration of T cells into the tumor. Concurrently, the ER-targeted delivery of PD-L1 siRNA resulted in the downregulation of both intracellular and membrane PD-L1 protein expression, consequently fostering the proliferation and activity of CD8+ T cells. Ultimately, the ER-targeted formulation exhibited enhanced anti-tumor efficacy and provoked anti-tumor immune responses against orthotopic colorectal tumors in vivo. Collectively, a robust ER-targeted delivery strategy provides an encouraging approach for achieving potent cancer chemoimmunotherapy.